Development of website-based e-poster learning media on the digestive system material of class XI MA Madani Alauddin Pao-Pao students - Nur Alamsyah; Ainul Uyuni Taufiq; Andi Tenri Ola Rivai (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
Rapid technological advances must be used optimally, especially in compiling learning media to create effective and efficient learning activities. This research aims to develop an e-poster learning media based on a website on digestion system material for grade XI of MA Madani Alauddin Pao-Pao that is valid, practical, and effective. This research uses the ADDIE development model's type of research and development. The developed product is tested through validity, practicality, and effectiveness tests. The subjects were 27 students of grade XI MIA MA Madani Alauddin Pao-Pao. The instruments used in the study were media validation sheets, student response questionnaires, educator response questionnaires, and learning outcomes test items. The results of the data analysis obtained a validity level of 3.60 (very valid), the practicality level of student responses is 3.18 (practical), and the educators' response is 3.06 (practical). Learning outcomes test students is 88.88% (effective). Based on the research, e-poster learning media based on a website on digestion system material deserves to be used. The result of the research is in the form of teaching media. Researchers hope that students can be motivated to learn independently and that teachers can make it easier to distribute the material being taught.Abstrak Kemajuan teknologi yang kian pesat perlu dimanfaatkan secara optimal, khususnya dalam menyusun media pembelajaran sehingga tercipta kegiatan belajar yang efektif dan efisien. Penelitian ini bertujuan untuk mengembangkan media pembelajaran e-poster berbasis website pada materi sistem pencernaan siswa kelas XI MA Madani Alauddin Pao-Pao yang bersifat valid, praktis, dan efektif. Penelitian ini menggunakan jenis penelitian dan pengembangan dengan model pengembangan ADDIE. Produk yang dikembangkan diuji melalui uji validitas, uji kepraktisan dan uji keefektifan. Subjek dalam penelitian ini adalah peserta didik kelas XI MIA MA Madani Alauddin Pao-Pao sebanyak 27 orang. Instrumen yang digunakan dalam penelitian adalah lembar validasi media, angket respon peserta didik, angket respon pendidik, dan butir-butir tes hasil belajar. Hasil penelitian menunjukkan bahwa media yang dikembangkan memiliki tingkat validitas yaitu 3.60 (sangat valid), tingkat kepraktisan berdasarkan penilaian respon peserta didik yaitu 3.18 (praktis) dan respon pendidik yaitu 3.06 (praktis). Tes hasil belajar peserta didik mencapai 88.88% (efektif), sehingga media pembelajaran e-poster berbasis website layak digunakan. Hasil penelitian berupa media ajar, peneliti berharap siswa termotivasi belajar secara mandiri dan bagi guru dapat memudahkan menyalurkan materi yang diajarkan.